Developing an Evidence-Based, Nurse-Led Psychoeducational Intervention With Peer Support in Gynecologic Oncology. Issue 2 (March 2016) - Bergin, Rebecca J.; Grogan, Suzi M.; Bernshaw, David; Juraskova, Ilona; Penberthy, Sylvia; Mileshkin, Linda R.; Krishnasamy, Meinir; Hocking, Alison C.; Aranda, Sanchia K.; Schofield, Penelope E.
Abstract : Background: The physical and psychosocial impact of radiotherapy for gynecologic cancer requires complex interventions to address treatment-related, psychosocial, and psychosexual and survivorship needs. A multidisciplinary approach is required to address these needs, but standard practice is varied and lacks a sound evidence base. Objective: The aim of this study was to describe the process of development and pilot testing of a novel evidence-based, complex psychoeducational intervention aiming to improve psychosocial outcomes for gynecologic-oncology patients treated curatively with radiotherapy. Methods: The intervention combines tailored nursing consultations with telephone peer support pretreatment, midtreatment, end of treatment, and posttreatment. The UK Medical Research Council framework for developing complex interventions was used to produce an evidence-based, feasible, and acceptable intervention. Results: Intervention manuals and study materials were informed by literature reviews of best-available evidence, relevant theory, and iterative consumer and expert consultations. The nurse manual specified content for consultations providing self-care information, coaching tailored to individual needs, and multidisciplinary care coordination. The peer manual described phone consultations aimed at providing psychosocial support and encouraging adherence to self-care strategies. Three peers and 1 nurse underwent rigorous skills and knowledge-based intervention delivery training. The intervention was pilot tested with 6 patients. Qualitative feedback led to minor design and content changes. Conclusions: The intervention was found to be feasible, relevant, and acceptable to participants and clinicians and is currently being tested in a national randomized controlled trial (PeNTAGOn). Implications for Practice: The Medical Research Council framework is useful in developing nursing interventions. The specific methods and strategies described are useful for designing future complex studies targeting patient supportive care.